No Difference Among Inhaled Anesthetics on the Growth and Metastasis of Murine 4T1 Breast Cancers in a Mouse Model of Spontaneous Metastasis - Liu, Qiuyue; Li, Ru; Lin, Jun (Frontiers in Pharmacology, 2022)
Objective: This study evaluates the effect of the commonly used inhaled anesthetics isoflurane, sevoflurane and desflurane on the viability and migration of murine 4T1 breast cancer cells, the growth and lung metastasis in a syngenetic model of spontaneous metastasis. Methods: The murine 4T1 breast cancer cells were exposed to isoflurane (2%), sevoflurane (3.6%), or desflurane (10.3%) for 3 hours. Cell viability was measured by MTT assay. The migratory capacity of 4T1 cells was assessed with a scratch assay after 24 hours incubation. Female balb/c mice were subjected to orthotopic implantation of 4T1 cells under anesthesia with one of the inhaled anesthetics: 2% isoflurane, 3.6% sevoflurane, or 10.3% desflurane. Subsequently resection of primary tumors was performed under the identical anesthetic used during implantation for 3 hours respectively. Three weeks later the mice were euthanized to harvest lungs for ex vivo bioluminescent imaging and histological analysis. Blood was collected for serum cytokine assays by ELISA. Results: There was no difference in cell viability among isoflurane, sevoflurane, desflurane and control groups (n = 180 for each group, P=0.648). Sevoflurane but not isoflurane or desflurane significantly increased the migration of 4T1 cells compared to the control group (n = 18, P = 0.024). There was no difference in the growth of the orthotopically implanted primary tumors (n = 12 for isoflurane group, n = 11 for sevoflurane group and for desflurane group, P=0.879). Surgical dissection of primary tumors in mice under anesthesia with isoflurane, sevoflurane, or desflurane led to no difference in lung metastasis following surgery (P=0.789). No significant difference was observed among isoflurane, sevoflurane, and desflurane groups in the serum levels of IL-6 (P=0.284), CCL-1 (P=0.591), MCP-1 (P=0.135), and VEGF (P=0.354). Conclusion: Our study demonstrated that sevoflurane increased the migration of 4T1 breast cancer cells in vitro. Inhaled anesthetics isoflurane, sevoflurane, and desflurane had no difference on the growth of primary tumor and the lung metastasis of 4T1 cells in the mouse model of spontaneous metastasis with surgical removal of primary tumors.